KINO’S BEHAVIOUR CHANGE AS REFLECTED THROUGH JOHN STEINBECK’S THE PEARL - SULISTYOWATI, RETNO (Jurnal Ilmiah Mahasiswa FIB, 2013)
According to Alexander’s notion about human’s mind, the process of creating imagination is developed day by day, and it makes people have something that they want to achieve. Sometimes it is realistic, but sometimes unrealistic, and it is called as wishes. Moreover, human’s wishes are depicted in a novel as the result of human’s imagination that reflects human’s behaviour through its character. John Steinbeck’s The Pearl portrays Kino’s behaviour change after finding a giant pearl. Then, based on this background, the theory of behaviour change uses to find out Kino’s behaviour change as depicted in the novel.The analysis reveals that Kino’s behaviour change because of his vanity of human wishes. First, he wants Coyotito to go to school; second, he wants to give a proper marriage for Juana in a church, and third, he wishes to have a rifle in order to have the same level with the Americans. The result of the study shows that Kino’s behaviour change because of his vanity of human wishes after he finds the giant pearl. He becomes cold hearted, ignorant, even kills people in order to protect his wishes.